Celebrity journalism – An oxymoron? Forms and functions of a genre. (February 2014) - Conboy, Martin
Debate about the ideal content or purpose of journalism is as old as print itself. The messy characteristics of popular culture have always intruded into the high principles and purposes of the communication of politics and journalism's intentions to provide information of importance for the public. In the intensity of the contemporary media era it is necessary to reconsider the interplay between celebrity news and journalism: beyond oxymoron and towards the appreciation of a paradox. This contribution seeks to explore some of the forms and functions of celebrity news in contemporary British culture and speculates on the increasing relevance of celebrity to the future of journalism.